Bridging the gap: An approach to reporting antimicrobial stewardship metrics specific to solid organ transplant recipients. Issue 5 (18th October 2022) - Greenlee, Sage B.; Acosta, Tommy J. Parraga; Makowski, Charles T.; Kenney, Rachel M.; Ramesh, Mayur; Williams, Jonathan D.; Alangaden, George J.
Abstract: Background: This study seeks to describe inpatient antimicrobial use (AU) utilizing the National Healthcare Safety Network‐AU (NHSN‐AU) framework among solid organ transplant recipients (SOTr) within 12 months after transplant. Methods: This cross‐sectional study included SOTr ≥ 18 years of age who underwent transplantation from January 2015 to December 2016 at a Midwestern US transplant center. Inpatient AU was followed for 12 months post‐transplant. Hospital days present up to 12 months post‐transplant, AU variables, and Clostridioides difficile infection (CDI) occurrences were analyzed. Results: The cohort of 530 SOTr included 225 kidney (42.5%), 171 liver (32.3%), 45 lung (8.5%), 40 heart (7.5%), 39 multivisceral (7.4%), seven small bowel (1.3%), and three pancreas (0.6%) transplants. Total days of therapy (DOT) were 22 782 among the cohort, with a median of 5 days [interquartile range [IQR], 1–12]. Lung and liver transplants had the most total DOT (6571 vs. 5569 days), while lungs and small bowels had the highest median DOT (13 [IQR, 2–56] vs. 12 [IQR, 2–31]). The facility‐wide DOT/1000 days were lowest in pancreas and highest in lung transplants (5.3 vs. 428.1). Small bowel transplants received the most resistant‐Gram‐positive infection and hospital‐onset infection agents for facility‐wide DOT/1000 days present. Pancreas and kidney transplants accounted for the most high‐risk CDI agents. CDI occurred in 34 patients, with kidney and liver transplants experiencing 13 each. Conclusion: This study represents one of the first reports of AU in SOTr utilizing the NHSN‐AU framework. More studies are needed for further peer‐to‐peer comparison of AU in this complex patient population. Abstract : This study evaluated antimicrobial use in SOTr up to 12‐months post‐transplant using NHSN‐AU reporting framework. Availability of SOTr specific metrics will aid in developing ASP quality initiatives and peer to peer comparison.